Patient profile in hemodialysis from a referral service in Rio Grande do Sul, Brazil (Research, Society and Development, 2022)
Objective: To identify the sociodemographic and clinical profile of patients with Chronic Kidney Disease undergoing hemodialysis in a reference service. Methodology: Quantitative, cross-sectional study with characteristics of a census. 94 patients with Chronic Kidney Disease (CKD) undergoing hemodialysis, linked to a nephrology service participated in this study. Data collection took place between September and October 2020, through nursing consultations, routine exams, medical records and structured questionnaires. Results: 94 patients were included in the study, with a mean age of 53.1 (± 13.7) years, prevalence of males (61.7%), married ​​ (45.7%), income from 1 to 2 minimum wages (46.8%), with incomplete primary education (62.8%), white (80.9%). As for clinical aspects, the main etiology of CKD was hypertension (43.6%), time since diagnosis on average 6.05 (± 6.46) years, venous access by arteriovenous fistula for hemodialysis (94.7%). The main complications were hypotension (56.4%) and cramps (28.7%). Conclusion: In the sample, was prevalent white men, married and with low education prevailed, with arterial hypertension being the main etiological factor. The variability of the findings points to the need for individualization of care for this population.